2014
DOI: 10.1007/s00417-014-2832-y
|View full text |Cite
|
Sign up to set email alerts
|

Association of the TLR4 signaling pathway in the retina of streptozotocin-induced diabetic rats

Abstract: Together, these data have demonstrated that TLR4 has a critical role in streptozotocin-induced diabetic retinopathy at the level of inflammatory cytokine induction, in both the MyD88-dependent and MyD88-independent pathways. TLR4 may become a new potential pharmacological target for treating diabetic retinopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 37 publications
7
24
0
Order By: Relevance
“…Furthermore, microglia express Toll-like receptor 4 (TLR4) (96,97), which is involved in the pathogenesis of different types of retinal degeneration (91,(96)(97)(98)(99). TLR4 activation has been shown to induce IL-18 mRNA and protein activation in renal tubular epithelial cells during renal obstruction (100).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, microglia express Toll-like receptor 4 (TLR4) (96,97), which is involved in the pathogenesis of different types of retinal degeneration (91,(96)(97)(98)(99). TLR4 activation has been shown to induce IL-18 mRNA and protein activation in renal tubular epithelial cells during renal obstruction (100).…”
Section: Discussionmentioning
confidence: 99%
“…Since cultured cells can have altered properties compared to their properties in their in vivo state, it may be that culturing conditions primed endothelial cells to respond pathologically to increasing RBP4 levels in our previous study. Interestingly, hyperglycemia increases TLR4 expression in endothelial cells (101) and the retinas of rats with STZ-induced diabetes (99), which could prime the endothelium to respond to proinflammatory levels of RBP4 during diabetes. Further studies are necessary to determine whether the elevation n.s., not significant by Student's t test; *, P Ͻ 0.05 by Student's t test; **, P Ͻ 0.01 by Student's t test; ***, P Ͻ 0.001 by Student's t test.…”
Section: Discussionmentioning
confidence: 99%
“…This was associated with decreased phosphorylation of NFkB, IL-6, and other inflammatory pathways [17]. Furthermore, work in the streptozotocin-induced diabetic rat showed that diabetes increased TLR4 signaling, leading to increased levels of key inflammatory mediators [18]. Taken together, there is literature to demonstrate localization and activation of TLR4 signaling in the retina, leading to retinopathy-associated complications.…”
Section: 0 Introductionmentioning
confidence: 99%
“…Inhibition of any of these factors shows promise in reducing retinal stress-associated neuronal and vascular damage [48]. Additionally, the role of the innate immune system may also contribute to retinal damage associated with diabetes, specifically toll-like receptor 4 (TLR4) [9, 10]. TLR4 is one of a class of pathogen-associated molecular pattern receptors [11].…”
Section: Introductionmentioning
confidence: 99%